Recycling of Acrylonitrile–Butadiene–Styrene Using Injection Moulding Machine. (2016) - García, María de Gracia Trujillo; Schlatter, Manfred; Cabrera, Francisco Mata; Manzanares, José Tejero; Hanafi, Issam
Abstract: ABS (Acrylonitrile Butadiene Styrene) is a thermoplastic resin commonly used for injection moulding applications. The effects of the recycling of ABS on mechanical properties were assessed. In this study, ABS was investigated in an attempt to overcome some of the barriers that currently hinder the progress of recycling activities. A recycling process was simulated in order to study the effects of recycling on mechanical properties of pure ABS with the injection moulding machine to create the specimens. Phase structure and mechanical properties of the ABS material were characterized by scanning digital microscope and tensile tests measurements. It was found that the effect of recycling on ABS is significant, in that change in tensile strengths and strains to failure were reduced considerably. Recycling of ABS caused no more deterioration in properties than occurred as a result of the first process.